Cross-Country Analysis of Auditor Specialization Premium: Effect of Legal, Extra-Legal and Political Environments - Bin, Sirinidhi (Institutional Knowledge at Singapore Management University, 2009)
Previous literature has provided mixed evidence of a premium in audit fee for industry-specialist auditors in US and other developed countries. In this cross-country study spanning twelve non-US countries, we provide evidence of such a premium in the international context, implying that specialist auditors provide a higher level of investor assurance than non-specialists. Further, we show that the average audit fee in countries with effective legal, extra-legal and political institutions is higher but the specialization premium is lower than in other countries. We interpret this finding as evidence that while effective institutions increase the demand for average level of audit assurance, they substitute rather than complement the incremental assurance provided by specialist auditors. This finding is reinforced by additional analysis that shows no significant specialization premium in the US, a country where institutions are most conducive to high financial statement assurance.